2022
DOI: 10.1111/1755-0998.13620
|View full text |Cite
|
Sign up to set email alerts
|

An ancient truncated duplication of the anti‐Müllerian hormone receptor type 2 gene is a potential conserved master sex determinant in the Pangasiidae catfish family

Abstract: The evolution of sex determination (SD) in teleosts is amazingly dynamic, as reflected by the variety of different master sex-determining genes identified. Pangasiids are economically important catfishes in South Asian countries, but little is known about their SD system. Here, we generated novel genomic resources for 12 Pangasiids and characterized their SD system. Based on a Pangasianodon hypophthalmus chromosomescale genome assembly, we identified an anti-Müllerian hormone receptor type Ⅱ gene (amhr2) dupli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 152 publications
1
14
0
Order By: Relevance
“…Genes annotated in the older stratum do not provide any other clear candidate for MSD in N. guentheri . It is, nonetheless, of note, that a single SNP that differentiated Y-linked amhr2 gene copy is located in the first exon which is consistent with the emerging role of mutations in its N-terminal domain crucial for ligand binding specifity in sex determination (Wen et al 2022; Kuhl et al 2023 and references therein).…”
Section: Discussionsupporting
confidence: 66%
“…Genes annotated in the older stratum do not provide any other clear candidate for MSD in N. guentheri . It is, nonetheless, of note, that a single SNP that differentiated Y-linked amhr2 gene copy is located in the first exon which is consistent with the emerging role of mutations in its N-terminal domain crucial for ligand binding specifity in sex determination (Wen et al 2022; Kuhl et al 2023 and references therein).…”
Section: Discussionsupporting
confidence: 66%
“…Sex determination systems with MSD evolved from duplications of the amh [10][11][12][13][14][15][16][17] or amhr2 [9,[18][19][20][21] genes have now been characterized in many fish species, all with a male-heterogametic system (XX/XY). In addition, the fact that Amh in monotremes [66], or Amhr2 in some lizards [67] are Y-linked also makes them strong MSD gene candidates in other vertebrate species.…”
Section: The Evolution Of Sex Determination In Perca and Sander Speci...mentioning
confidence: 99%
“…For instance, amh has been characterized or suspected to be the MSD gene in pikes [11,12], Nile tilapia [13], lumpfish [14], Sebastes rockfish [15], lingcod [16], and Patagonian pejerrey [17]. The cognate receptor gene of Amh, amhr2, has also been found as a potential MSD gene in Pangasiidae [18], Takifugu [19], Ayu [20], common seadragon and alligator pipefish [21], as well as in yellow perch [9]. The repeated and independent recruitment of TGF-β receptors, including Amhr2 , in teleost fish sex determination is even more puzzling as many of these MSD genes, encoding a TGFβ receptor, share a similar N-terminal truncation [9,18,21], supporting their evolution towards a ligand-independent mechanism of action [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fish display highly diverse chromosome SD systems (Cioffi et al, 2017) and several master SD genes have been reported in this group (Martínez et al, 2014). Among them are: classical transcription factors such as dmy (Matsuda et al, 2002; Wang et al, 2022), sox3 (Takehana et al, 2014) or sox2 (Martínez et al, 2021); transforming growth factor β‐related genes such as gsdf (Herpin et al, 2021; Myosho et al, 2012) or amh (Hattori et al, 2012; Pan et al, 2019) and its receptor amhr2 (Feron et al, 2020; Kamiya et al, 2012; Nacif et al, 2022; Nakamoto et al, 2021; Wen et al, 2022; Zheng et al, 2022); genes related to the steroidogenic pathway such as bcar1 (Bao et al, 2019) or hsd17b1 (Koyama et al, 2019); and, finally, some unexpected, such as the interferon‐related sdY gene in salmonids (Yano et al, 2013). The recent identification of several master SD genes in this group has been associated with the highly contiguous and reliable chromosome‐level genome assemblies achieved via improvements in long‐read sequencing technologies, scaffolding and bioinformatic approaches (Ramos & Antunes, 2022).…”
Section: Introductionmentioning
confidence: 99%